1978
DOI: 10.1113/expphysiol.1978.sp002418
|View full text |Cite
|
Sign up to set email alerts
|

Effect of High Fluoride Intake on Haematological Aspects of the Mouse

Abstract: The effect of feeding adult Swiss albino mice of both sexes a diet supplemented with 0, 125, 250 and 500 parts/106 of fluoride for four and eight week periods on haemoglobin concentration (Hb), packed cell volume (PCV) and mean corpuscular haemoglobin concentration (MCHC) was investigated. Values of the three parameters were significantly lowered at both periods in the treated groups as compared with the controls. The extent of reduction in these values was, in general, dependent on the dose of supplemented … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

1980
1980
2010
2010

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 5 publications
1
3
0
Order By: Relevance
“…However, appearance of the symptoms in selenium exposed cattle did change the trend in the above values. In accordance with our findings, Susheela et al (1983) and Mehdi et al (1978) reported on the influence of erythrocyte parameters and showed similar decremental changes in rabbit and mouse. Being a cumulative poison, fluoride induces many metabolic disturbances in different organs, blood being the primary target , with bone and teeth being the second deposition site (McDowell, 1992).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…However, appearance of the symptoms in selenium exposed cattle did change the trend in the above values. In accordance with our findings, Susheela et al (1983) and Mehdi et al (1978) reported on the influence of erythrocyte parameters and showed similar decremental changes in rabbit and mouse. Being a cumulative poison, fluoride induces many metabolic disturbances in different organs, blood being the primary target , with bone and teeth being the second deposition site (McDowell, 1992).…”
Section: Discussionsupporting
confidence: 93%
“…Bober et al (2001) also found in humans that fluoride caused a decrease in Na + -H + exchanger activity and an increase in intracellular H + ion concentration. Mehdi et al (1978) suggested from mouse studies that hemoglobin, packed cell volume and mean corpuscular hemoglobin concentration values could serve to detect preclinical effects of high fluoride intake with an added dose of as low as 125 mg/kg, or even less, for a period of four weeks or probably earlier. Han et al (2002 reported from cattle studies that fluoride caused a decreased erythrocyte activity of superoxide dismutase, glutathione peroxidase and catalase and an increased content of free radicals and malonaldehyde during long-term intake of an overdose of fluoride.…”
Section: Introductionmentioning
confidence: 99%
“…Acute (one or a few large doses) ( 72) Biochemical and cytological effects (15, 38, 85,103) The mechanism(s) for some of the toxic effects of fluoride are known, e.g. the neuromuscular effects (spasms) are caused by fluoride binding to Ca+ -I-in plasma and thereby lowering the Ca+ -Iconcentration (1 1 , 1 10).…”
Section: VIIImentioning
confidence: 99%
“…Effects vary depending upon fluoride dose, duration of exposure, and species, and include anemia and leukopenia (Mehdi et al, 1978;Eren et al, 2005). At modest in vitro concentrations (< 500 μM), NaF has been shown to promote the differentiation of human promyelocytic tumor cells (HL-60) to granulocyte-like cells (Kawase et al, 1996).…”
Section: Effects On Hematopoietic Cells and Hematopoiesismentioning
confidence: 99%